2022
DOI: 10.3390/ijerph192013544
|View full text |Cite
|
Sign up to set email alerts
|

Personal Traits of the People Who Help: The Case of Bystanders to Violence against Women

Abstract: Within the context of emergency situations, the terms witness or bystander are used to refer to individuals involved in oppressive incidents who are neither the victim nor the perpetrator. Among the different types of emergency situations, our study focuses on violence against women (VAW). In keeping with current efforts in the scientific literature on bystander intervention and the evidence currently available, the main focus of this study is to analyze some personal factors that reflect the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
(118 reference statements)
0
0
0
Order By: Relevance
“…The primary analysis only showed gender differences while controlling for age in negative emotions, but it also showed minor effects and small differences. We must acknowledge that gender could be an important predictor, since girls have a more empathetic attitude and are more supportive in helping situations [ 15 , 16 , 17 ]. Investigating only age was found to be positively correlated with first aid willingness for strangers and knowledge and negatively with negative emotions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary analysis only showed gender differences while controlling for age in negative emotions, but it also showed minor effects and small differences. We must acknowledge that gender could be an important predictor, since girls have a more empathetic attitude and are more supportive in helping situations [ 15 , 16 , 17 ]. Investigating only age was found to be positively correlated with first aid willingness for strangers and knowledge and negatively with negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, girls and older individuals have an increased willingness to help as well [ 9 , 14 ]. Previous studies have found that girls have a more empathic attitude than males in helping behavior, and they react more strongly and are more supportive in these situations [ 15 , 16 , 17 ]. The role of age in helping is mainly associated with knowledge and training in first aid, since older individuals are more likely to have had previous first aid experience.…”
Section: Introductionmentioning
confidence: 99%